Transcription factor Sox9 exacerbates kidney injury through inhibition of microRNA-96-5p and activation of the Trib3/IL-6 axis - Xiao Wang; Guang Chen; Yongqiang Du; Jiajia Yang; Wei Wang (Karger Publishers, 2023)
Introduction: Our study investigated the possible mechanisms of the role of the transcription factor Sox9 in the development and progression of kidney injury through regulation of the miR-96-5p/Trib3/IL-6 axis. Methods: Bioinformatics analysis was performed to identify differentially expressed genes in kidney injury and normal tissues. An in vivo animal model of kidney injury and an in vitro cellular model of kidney injury were constructed using LPS induction in 8-week-old female C57BL/6 mice and human normal renal tubular epithelial cells HK-2 for studying the possible roles of Sox9, miR-96-5p, Trib3, and IL-6 in kidney injury. Results: Sox9 was highly expressed in both mouse and cellular models of kidney injury. Sox9 was significantly enriched in the promoter region of miR-96-5p and repressed miR-96-5p expression. Trib3 was highly expressed in both mouse and cellular models of kidney injury and promoted inflammatory responses and kidney injury. In addition, Trib3 promoted IL-6 expression, which was highly expressed in kidney injury and promoted the inflammatory response and extent of injury in kidney tissue. In vivo and in vitro experiments confirmed that the knockdown of Sox9 improved the inflammatory response and fibrosis of mouse kidney tissues and HK-2 cells, while the ameliorative effect of silencing Sox9 was inhibited by overexpression of IL-6. Conclusion: Collectively, Sox9 up-regulates miR-96-5p-mediated Trib3 and activates the IL-6 signaling pathway to exacerbate the inflammatory response, ultimately promoting the development and progression of kidney injury.